Head-shaking tilt suppression: a clinical test to discern central from peripheral causes of vertigo - Zuma e Maia, F. C.; Cal, Renato; D’Albora, Ricardo; Carmona, Sergio; Schubert, Michael C. (Journal of neurology, 2017)
Tilt suppression refers to both tilting the head away from an Earth vertical axis and a reduction of an induced horizontal nystagmus. This phenomenon of reducing an induced horizontal nystagmus involves a circuitry of neurons within the vestibular nuclei and the cerebellum (collectively referred to as velocity storage) and signals from the otolith end organs. Lesions involving this circuitry can disrupt tilt suppression of induced horizontal nystagmus. We investigated the clinical value of combining the horizontal head-shaking nystagmus test with tilt suppression in 28 patients with unilateral peripheral vestibular hypofunction and 11 patients with lesions affecting the central nervous system. Each of the subjects with peripheral vestibular lesions generated an appropriately directed horizontal nystagmus after head shaking that then suppressed the induced angular slow phase velocity on average 52 ± 17.6% following tilt down of the head. In contrast, patients with central lesions had very little ability to suppress post-head-shaking nystagmus (mean 3.4 ± 56%). We recommend tilting the head after head shaking as a useful clinical test to assist in the differential diagnosis of vertiginous patients. In the case of unilateral peripheral vestibular hypofunction, head tilt suppresses the induced nystagmus via influence of the otolith organ. In the case of central pathology, the inability to suppress the nystagmus is from lesions impairing the otolith mediation on the velocity storage circuitry.